Oxidative stress and retinopathy: evidence from epidemiological studies - Xiangliang Liu; Yu Chang; Yuguang Li; Yingrui Liu; Wei Song; Jin Lu; Naifei Chen; Jiuwei Cui (Journal of Translational Medicine)
Abstract Background Previous studies have suggested oxidative stress may play a key role in the pathogenesis of retinopathy, while evidence from observational studies directly linking oxidative biomarkers to clinically relevant outcomes has been limited. This study aims to investigate the association between oxidative balance score (OBS) and prevalence of retinopathy in a nationally representative sample of U.S. adults, including both those with and without diabetes. Methods Data were obtained from the NHANES 2005–2008, including 3,287 participants. OBS was calculated from 16 dietary and 4 lifestyle components and categorized into tertiles. Weighted logistic regression was used to assess the association between OBS and retinopathy in the overall, diabetic, and non-diabetic populations, and Cox proportional hazards models evaluated the link between OBS and all-cause mortality in those with retinopathy. Restricted cubic spline (RCS) analysis explored the dose-response relationship between OBS and retinopathy. Subgroup analyses and interaction tests were conducted based on age, sex, race, BMI, education level, and diabetes status. Results Participants in the highest OBS tertile had a 28% lower risk of retinopathy compared to those in the lowest tertile (OR 0.72, 95% CI 0.54–0.95, P = 0.023). RCS analysis showed a significant overall association between higher OBS and reduced retinopathy risk, without a nonlinear pattern. In participants with retinopathy, higher OBS was linked to a 60% reduction in all-cause mortality (HR 0.40, 95% CI 0.24–0.66, P < 0.001). Subgroup analysis revealed stronger inverse associations between OBS and retinopathy in younger individuals and those with higher education, with a significant interaction between OBS and age (P for interaction < 0.05). Conclusion Our study provides evidence that higher cumulative antioxidant exposure assessed by OBS is associated with a reduced risk and severity of retinopathy and lower all-cause mortality in U.S. adults with retinopathy, highlighting the importance of maintaining a favorable oxidative balance in retinal health.